Dom Helder Camara e o teatro popular dos Coelhos: uma ação pastoral libertadora. - Saldanha, Stela Maris (2019)
In 1968, the Popular Theater of Coelhos ( Teatro Popular dos Coelhos, TPC) was born in Recife, in a waterlogged area. Since its inception it has been linked to Operation Hope (Operação Esperança), of the Archdiocese of Olinda and Recife, entity directed to the organization of the communities of low income, in which TPC wanted emancipatory actions. The TPC remained attached to the Archdiocese while Archbishop Helder Camara lasted. During this period, he developed cultural and mobilization activities, being the oldest community theater group integrated to the pastoral projects of the Church in Pernambuco, between 1964 and 1985. During the period of the Brazilian civil-military dictatorship, it was a focus of resistance to social exclusion of peripheral segments of the population. At the same time, it reflected a new praxis of the Catholic institution, intended since the Second Vatican Council. The survival of TPC to adversity can also be credited to Dom Helder's personal commitment to the art of representation, to be among the resources available for evangelism. This research focuses on the trajectory of the Teatro Popular dos Coelhos, whose memory is submerged, although at the moment of its realization it has guaranteed for itself a place as a political, artistic and evangelizing subject. The relation between religion and theater appears theorized in this work from two basic concepts: the theater of catechesis and the theater of evangelization. The first aimed to fit new communities to a world that was wanted to be immutable, and the latter, here taking as reference the TPC itself was to transform the world by producing insurgent narratives. The profile not only conceptual but mainly investigative and intended memory-building in this dissertation gave him, as a structural support, besides bibliographical consultations, the collection of personal testimonies, without which it would not have been possible to reconstiture, though partially, the history of the Popular Theater of Coelhos.